Kinetic analysis of synaptonemal complex dynamics during meiosis of yeast Saccharomyces cerevisiae reveals biphasic growth and abortive disassembly - Pollard, Michael G.; Rockmill, Beth; Oke, Ashwini; Anderson, Carol M.; Fung, Jennifer C. (Frontiers in Cell and Developmental Biology, 2023)
The synaptonemal complex (SC) is a dynamic structure formed between chromosomes during meiosis which stabilizes and supports many essential meiotic processes such as pairing and recombination. In budding yeast, Zip1 is a functionally conserved element of the SC that is important for synapsis. Here, we directly measure the kinetics of Zip1-GFP assembly and disassembly in live cells of the yeast S. cerevisiae. The imaging of SC assembly in yeast is challenging due to the large number of chromosomes packed into a small nucleus. We employ a zip3Δ mutant in which only a few chromosomes undergo synapsis at any given time, initiating from a single site on each chromosome, thus allowing the assembly and disassembly kinetics of single SCs to be accurately monitored in living cells. SC assembly occurs with both monophasic and biphasic kinetics, in contrast to the strictly monophasic assembly seen in C. elegans. In wild-type cells, once maximal synapsis is achieved, programmed final disassembly rapidly follows, as Zip1 protein is actively degraded. In zip3Δ, this period is extended and final disassembly is prolonged. Besides final disassembly, we found novel disassembly events involving mostly short SCs that disappeared in advance of programmed final disassembly, which we termed “abortive disassembly.” Abortive disassembly is distinct from final disassembly in that it occurs when Zip1 protein levels are still high, and exhibits a much slower rate of disassembly, suggesting a different mechanism for removal in the two types of disassembly. We speculate that abortive disassembly events represent defective or stalled SCs, possibly representing SC formation between non-homologs, that is then targeted for dissolution. These results reveal novel aspects of SC assembly and disassembly, potentially providing evidence of additional regulatory pathways controlling not just the assembly, but also the disassembly, of this complex cellular structure.